Korelasi Tingkat Stres dengan Siklus Menstruasi pada Mahasiswi Keperawatan: Correlation of Stress Levels with Menstrual Cycles in Nursing Students - Umi Aniroh; Laeli Fitriyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2024)
The menstrual cycle is said to be abnormal if it is <21 days or >35 days. The impact of an abnormal menstrual cycle, if not treated immediately, can increase the risk of reproductive system diseases such as fertility disorders, infertility, uterine polyps and ovarian cysts. In Indonesia, 14.4% of women experience irregular menstrual cycles. One of the factors that causes menstrual cycle disorders is stress. Stress is often experienced by female students, where this group is undergoing a transitional and critical phase before living life in society. The aim of this research was to determine the relationship between stress levels and the menstrual cycle of female students in the Bachelor of Nursing Study Program at Ngudi Waluyo University. This research design is descriptive correlative with a cross-sectional approach. The sampling technique used in this research was a total sample with research subjects totaling 62 respondents. The measuring tool used in data collection was the DASS 42 questionnaire. Univariate analysis to describe the frequency distribution of stress levels and menstrual cycles, bivariate analysis to find the relationship between the two variables above using the Rank-Spearman test. Respondents experienced more moderate stress as many as 22 people (35.5%) and the highest menstrual cycle of respondents was oligomenorrhea as many as 29 people (46.8%). The results of the analysis showed a correlation value of r = 0.091, p-value = 0.481 (p > 0.05), which means there is no relationship between stress levels and female students' menstrual cycles. Respondents are expected to be able to maintain both physical and mental health, maintain good nutritional intake, exercise regularly and maintain their weight so that their menstrual cycle is not disrupted. ABSTRAK Siklus menstruasi dikatakan tidak normal apabila <21 hari atau >35 hari. Dampak siklus menstruasi yang tidak normal, jika tidak segera ditangani dapat meningkatkan risiko gangguan penyakit sistem reproduksi seperti gangguan kesuburan, infertilitas, polip rahim dan kista ovarium. Di Indonesia perempuan yang mengalami masalah siklus menstruasi tidak teratur sebanyak 14,4%. Salah satu faktor yang menyebabkan gangguan siklus menstruasi yaitu stres. Stres sering dialami oleh mahasiswi, dimana kelompok ini sedang menjalani fase transisi dan kritis sebelum menjalani kehidupan di masyarakat. Tujuan penelitian ini untuk mengetahui hubungan tingkat stres dengan siklus menstruasi mahasiswi pada Program Studi S1 Keperawatan Universitas Ngudi Waluyo. Desain penelitian ini deskriptif korelatif dengan pendekatan Cross-Sectional. Teknik pengambilan sampel yang digunakan dalam penelitian ini adalah total sampel dengan subjek penelitian sejumlah 62 responden. Alat ukur yang digunakan dalam pengambilan data adalah kuesioner DASS 42. Analisa univariat untuk menggambarkan distribusi frekuensi tingkat stres dan siklus menstruasi, analisis bivariat untuk mencari hubungan kedua variabel diatas dengan menggunakan uji Rank-Spearman. Responden lebih banyak mengalami stres sedang sebanyak 22 orang (35,5%) dan siklus menstruasi responden terbanyak adalah oligomenorea sebanyak 29 orang (46,8%). Hasil analisis diperoleh hasil nilai korelasi r = 0,091, p-value = 0,481 (p > 0,05) yang artinya tidak terdapat hubungan antara tingkat stres dengan siklus menstruasi mahasiswi. Responden diharapkan dapat menjaga kesehatan baik fisik maupun mental, menjaga asupan nutrisi yang baik, melakukan olah raga secara rutin serta menjaga berat badannya agar siklus menstruasi tidak terganggu.